SAMARINDA JUNIOR HIGH SCHOOL TEACHERS' COMMITMENT: THE IMPACT OF ORGANISATIONAL CULTURE, LEADERSHIP STYLE, MORAL HIERARCHY LEVEL, AND MOTIVATION - Dwiyono, Yudo; Kurniawan, Dydik; Heriansyah, Masnurrima; Atmaja, A.A. Bagus Surya (Sekolah Tinggi Ilmu Ekonomi Sultan Agung Pematangsiantar, 2024)
The goal of this study is to investigate a model of the direct variable relationships between organisational culture, moral hierarchy levels, commitment, motivation, and leadership style. Purpose This study is to find out, the direct influence of school organizational culture, the leadership style of the principal, on teacher commitment, the level of moral hierarchy on teacher commitment, teacher work motivation on teacher commitment, the direct influence of school organizational culture, the principal's leadership style on teacher work motivation, the level of moral hierarchy on teacher work motivation. The study population of all junior high school teachers in Samarinda City. The sampling technique is used non-random, proportional sampling. This technique is to obtain 309 samples from the total population 796 teachers. Path analysis is one analysis technique used to find the relationship between variables. The stages of path analysis techniques are (1) Descriptive statistical analysis, (2) Normality test requirements test and linearity test, (3) Hypothesis test using significance test analysis. Based on the results, it can be said that raising work motivation, moral hierarchy level, leadership style, and organisational culture of the school can all help junior high school teachers in Samarinda become more committed.